Islamic Religious Education Learning Innovation: The Role and Challenges of the Joyful Learning Approach - Hasfiana, Hasfiana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Islamic Religious Education learning is still largely dominated by lectures and memorization methods, which create a monotonous classroom atmosphere and lack active student engagement. This condition affects learning interest and the effectiveness of internalizing religious values. This study aims to examine the application of Joyful Learning as an innovation in Islamic Religious Education learning. The method used is a literature study with a descriptive qualitative approach with a time span of the last 10 years based on Google Scholar. Data were collected through a review of various relevant scientific literature sources, then analyzed thematically. The results show that Joyful Learning can increase student interest, understanding, and engagement through the use of methods such as educational games, digital media, group discussions, and experiential learning. Despite its great potential, the implementation of Joyful Learning faces various challenges such as limited facilities, teacher readiness, and classroom dynamics. Solutions offered include teacher training, the use of simple media, and collaboration with parents and the school community. The conclusion of this study is that Joyful Learning has a strategic role in reconstructing Islamic Religious Education learning to be more contextual, enjoyable, and meaningful. Students who are not only intellectually intelligent, but also have noble character and love the teachings of Islam.